Evaluation of anti-parkinsonian activity of Elaeocarpus ganitrus on haloperidol induced Parkinson’s disease in mice - Bagewadi, Harish G.; Khan, A. K. Afzal (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Elaeocarpus ganitrus (Family: Elaeocarpaceae), has been used for the treatment of depression, convulsions and asthma. The existing literature is lacking in studies showing anti-parkinson effect of E. ganitrus. There is increased concern about the side-effects of conventional medicine in the treatment of Parkinson’s disease (PD). Hence E. ganitrus having anti-oxidative property may be a safer alternative. Methods: To evaluate the anti-parkinson effect of E. ganitrus, rota rod and catalepsy bar tests were used. Assessment of oxidative stress was done by measuring the malondialdehyde (MDA) and reduced glutathione (GSH) levels in the striatal region of the brain. One-way ANOVA was used to detect statistical significance, followed by post-hoc Tukey test. Results: E. ganitrus (200 and 400 mg/kg, p.o.) pretreated groups significantly increased the retention time in rota rod test (p<0.001) and significantly decreased the latency period in catalepsy bar test (p<0.001), when compared with haloperidol treated group alone. E. ganitrus (200 and 400 mg/kg, p.o.) pretreated groups showed significant anti-oxidative effect by causing a decrease in brain MDA levels (p<0.001) and a significant increase in GSH levels (p<0.001). Conclusions: Oxidative stress plays a vital role in the pathophysiology of PD. The results of this study conclusively show that E. ganitrus has anti-oxidant activity and neuroprotective activity in haloperidol experimental model of PD.